2016
DOI: 10.5713/ajas.15.1053
|View full text |Cite
|
Sign up to set email alerts
|

Marination and Physicochemical Characteristics of Vacuum-aged Duck Breast Meat

Abstract: We investigated marinade absorption and physicochemical characteristics of vacuum-aged duck breasts that were halved and individually vacuum-packed for chiller aging at 4°C for 14 d. One half was marinated for 0, 7, or 14 d, while the second half was used as a control. Marinade absorption, cooking loss, cooking yield, texture profile, pH, color, protein solubility, and thiobarbituric acid reactive substances (TBARS) values were evaluated, and protein sodium dodecyl sulfate–polyacrylamide gel electrophoresis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
11
2
Order By: Relevance
“…As shown in Figure 1, the high water content of sample SV45 could be due to protein solubility. According to Khan et al [34], high water holding capacity (WHC) and cooking yield are related to high protein solubility. The review by Hamm [35] indicates many of researchers have found that most sarcoplasmic proteins aggregate between 40°C and 60°C.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, the high water content of sample SV45 could be due to protein solubility. According to Khan et al [34], high water holding capacity (WHC) and cooking yield are related to high protein solubility. The review by Hamm [35] indicates many of researchers have found that most sarcoplasmic proteins aggregate between 40°C and 60°C.…”
Section: Resultsmentioning
confidence: 99%
“…After boiling, the samples were surface dried, and weighed. Cooking loss was determined by expressing weight of cooked sample (B) as a percentage of the precooked sample (A): ( Khan et al, 2016) Proximate composition was determined after removing the skin and external fat from the breast (pectoralis major) meats according to procedures of the AOAC International (2005). Total fat was determined by the AOCS standard procedure Am 5-04 (Ankom, 2001) in which the Ankom XT10 extraction system was used.…”
Section: Methodsmentioning
confidence: 99%
“…We used the shear force measurement by Khan et al (2016) with slight modifications. For analysis of shear force, meat samples (100 g) were vacuum packed using an impermeable polyethylene bag (HFV-600L, Hankook Fujee Industries Co., Ltd., Korea), cooked in a water bath until the core temperature reached 72°C, and cooled in iced water until they reached room temperature.…”
Section: Methodsmentioning
confidence: 99%